Molecular structure, spectroscopic (UV-vis, FT-IR and FT- Raman), conformational aspects of 3t-pentyl-2r,6c-di(naphthalen-1-yl) piperidin-4-one oxime: a comprehensive experimental and DFT study - Anandhy, K.; Arockia doss, M.; Amala, S.; Mahalakshmi, S.; Rajarajan, G. (International Journal of Advanced Chemistry, 2017)
The molecular structure and conformational aspects of 3t-pentyl-2r,6c-di(naphthalen-1-yl)piperidin-4-one oxime (3-PDNPO) were studied by using B3LYP level with 6-31G(d,p) p basis set. The optimized geometrical parameters are in agreement with analogue available single XRD data. The optimized parameters showed that the piperidin-4-one ring adopts chair conformation.The FT- IR and FT-Raman spectra were recorded within the region 4000-400 cm-1 and 4000-10 cm-1, respectively. It was found by experimental wavenumbers and DFT wavenumbers were in good agreement. Electronic properties are investigated using TD-DFT/B3LYP method using 6-31G (d,p) basis set and compared with experimental UV-visible spectra. Additionally, the Î”E gap investigated three phases follows the order of CHCl3 > gas > Methanol. The favourite sites for substitution reactions were evaluated by Mulliken and MEP analyses. From NLO analysis, it is found that the hyperpolarizability values are two times greater than the urea.Our proposed simulation procedure offers an alternative compound with which we can evaluate or design the best candidate NLO material.